Rancang Bangun Aplikasi ‘ekoSaku’ dengan Menggunakan Metode Design Thinking - Ni Luh Juli Yetti; I Ketut Gede Suhartana; Ida Bagus Gede Sarasvananda (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Indonesia continues to face serious waste management issues, particularly with non-organic waste. According to the National Waste Management Information System (SIPSN), the total waste generation in 2024 reached 34,214,607.36 tons across 317 districts and cities. This study presents the design of a mobile-based application called ekoSaku, aimed at facilitating the digital collection and exchange of recyclable waste between users and agents. The development process applies the Design Thinking methodology, consisting of five stages: empathize, define, ideate, prototype, and test. User needs were identified through questionnaires distributed to 15 respondents, focusing on daily waste-handling behavior and digital expectations. These insights shaped the app’s core features such as waste photo uploads, home pickups, price setting by agents, transaction tracking, and a point-based reward system. The prototype was evaluated using the System Usability Scale (SUS), with an average score of 81, indicating excellent usability. The results show that ekoSaku offers a user-friendly and effective approach to digital waste management.